(untitled) (World Bulletin of Social Sciences, 2026)
This study explores the design of technology lessons aimed at developing students’ motor skills, particularly in primary education. It highlights the importance of integrating practical activities, didactic games, and innovative teaching methods to enhance fine and gross motor abilities. The research emphasizes learner-centered approaches, creativity, and competency-based education. By analyzing modern pedagogical strategies, the study demonstrates how structured lesson planning can improve coordination, cognitive engagement, and overall student performance. The findings provide practical recommendations for teachers to effectively organize technology lessons focused on motor skill development.